ANALISIS KOINTEGRASI DAN PERAMALAN DAMPAK HARGA MINYAK DUNIA TERHADAP INDIKATOR EKONOMI MAKRO INDONESIA - I Made Rinaldi Prasetya; I Wayan Sukadana (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2023)
Indonesia still depends on oil imports from outside to meet domestic oil needs. Seeing fluctuations in world oil prices made researchers want to research long-term and short-term analyses of the impact of world oil price movements on inflation, the rupiah exchange rate, and IHSG. This study uses monthly data from January 1, 2016, to December 31, 2022, to analyze the influence of global oil prices on the inflation rate, exchange rate, and IHSG (Indonesia Stock Exchange Composite Index) in Indonesia. The analysis method employed is Vector Autoregressive (VAR) with the assistance of Eviews 12. The research findings indicate that in the long run, global oil prices significantly positively influence the inflation rate in Indonesia. However, in the short run, the influence is not statistically significant in a positive direction. Furthermore, global oil prices significantly negatively influence the value of the Indonesian rupiah against the US dollar and the level of the IHSG in the long run. However, in the short run, the influence is not statistically significant in a negative direction on the value of the rupiah and the IHSG level..